The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.35663/amp.2020.372.999
|View full text |Cite
|
Sign up to set email alerts
|

Educación médica durante la pandemia delEducación médica durante la pandemia del COVID -19: iniciativas mundiales para el pregrado, internado y el residentado médico COVID -19: iniciativas mundiales para el pregrado, internado y el residentado médico

Abstract: La pandemia de enfermedad por coronavirus de 2019 (COVID-19) ha planteado diversos retos a los estamentos de la sociedad y la educación médica no ha sido la excepción. A nivel mundial, las universidades han planteado diversas iniciativas en el pregrado y el internado medico como la virtualización parcial de su contenido curricular, la modificación de su currículo y las actividades educativas y la incorporación de estudiantes de los últimos años a las actividades asistenciales. En el residentado médico, las esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
3
0
3
Order By: Relevance
“…This study compared school performance and pass rates of regular examinations in phase one of the 2010 MB curriculum in the 2019 and 2020 school years. It was observed that, following the restructuring of assessment methods in the face of the pandemic by COVID-19, there was an 8.89% increase in student pass rates in 2020 in the first year, while in the second year it was 1.21%; it should be noted that each country has implemented educational tools in response to its possibilities and needs for this type of modality used by the health emergency (Herrera and Toro, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study compared school performance and pass rates of regular examinations in phase one of the 2010 MB curriculum in the 2019 and 2020 school years. It was observed that, following the restructuring of assessment methods in the face of the pandemic by COVID-19, there was an 8.89% increase in student pass rates in 2020 in the first year, while in the second year it was 1.21%; it should be noted that each country has implemented educational tools in response to its possibilities and needs for this type of modality used by the health emergency (Herrera and Toro, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Un estudio realizado en India mostró que el 50% de estudiantes de medicina consideraba que las clases presenciales eran mejores. Mientras que otro estudio señaló que la modalidad mixta (clases virtuales y presenciales) mejoró el desempeño de estudiantes [23]. En México, con relación al ámbito escolar encontró que el 49% del estudiantado manifestó sentirse sumamente satisfecho con los resultados obtenidos durante el período, el 28% medianamente y solo un 23% se sintió insatisfecho con los resultados [24].…”
Section: Cambios a Nivel Académico Y De Aprendizajeunclassified
“…Un estudio realizado en India mostró que el 50% de estudiantes de medicina consideraba que las clases presenciales eran mejores. Mientras que otro estudio señaló que la modalidad mixta (clases virtuales y presenciales) mejoró el desempeño de estudiantes (12). En México, con relación al ámbito escolar encontró que el 49% del estudiantado manifestó sentirse sumamente satisfecho con los resultados obtenidos durante el período, el 28% medianamente y solo un 23% se sintió insatisfecho con los resultados (21).…”
Section: Cambios a Nivel Académico Y De Aprendizajeunclassified